UJI SPF DAUN KESUM (Polygonum minus Huds) PADA BEBERAPA PELARUT MENGGUNAKAN SPEKTROFOTOMETRI UV-Vis - Dian Kartikasari; Rifki Fahmi; Ika Ristia Rahman; Hairunnisa; Abduh Ridha (Akademi Farmasi Yarsi Pontianak, 2023)
Kesum leaves (polygonum minus huds) have many benefits. Kesum leaves contain useful compounds such as alkaloids, flavonoids, and phenolics which can protect against free radicals caused by UV rays and absorb UV rays. This study used the UV-Vis spectrophotometry method. Absorbance was measured at a wavelength of 290-320 nm. The determination of the SPF value is based on the Mansur equation. The test results showed that the ethanol extract of daun kesum (polygonum minus huds) had SPF activity on methanol extract (22.803), 50% ethanol extract (20.0606), 70% ethanol extract (24.36), and 96% ethanol extract (25). ,8416) all belong to the ultra protection class.